Experimental research of wear intensitivity of 9 mm pistol barrel with the use of long-term storage ammunition - Biryukov, Alexey; Gurnovich, Anatoliy; Biryukov, Igor (Technology audit and production reserves, 2017)
The process of deteriorating the ballistic characteristics of barreled weapons in general and pistols in particular is directly proportional to the barrel bore wear process. The use of long-term storage ammunition, in comparison with the guarantee ammunition, aggravates the patterns of deterioration of ballistic characteristics and increase in the wear rate of the pistol barrel on the number of shots. On the basis of the obtained patterns, the dependences of the increase in barrel wear and the decrease in the initial bullet velocity from the ammunition storage period are established. The maximum ammunition storage period in 28.92 years is predicted, the use of which will not lead to a decrease in the minimum allowable initial bullet velocity (299.25 m/s) within the established barrel resource. A possible error in the forecast is determined at 25.2 %, and therefore ammunition storage period without decrease in the minimum allowable initial bullet velocity is reduced to 21.63 years.